Comparing the effects of zinc sulfate, calcium pantothenate, their combination and minoxidil solution regimens on controlling hair loss in women: A randomized controlled trial - Mansour Siavash; Fereshteh Tavakoli; Fatemeh Mokhtari (Journal of Research in Pharmacy Practice, 2017)
Objective: This study was conducted to evaluate the combination of oral supplements with 2% minoxidil solution in four groups of women with hair loss. Methods: A prospective, randomized controlled trial was conducted from July to December 2016 in dermatology clinics affiliated to Isfahan University of Medical Sciences. A total of 73, 15–45-year-old, women with hair loss participated in this 4-month study. Simple randomization using Random Allocation Software was done to put the participants in four groups to receive coadministration of zinc sulfate and calcium pantothenate, zinc sulfate, calcium pantothenate, and 2% minoxidil solution. The primary endpoint was the change in hair density and diameter measured by dermatoscope. Secondary endpoints included the researcher's evaluation, dermatologist's opinion - which was blinded to the study - from comparing the participants' photographs before and after treatment and finally, overall changes in hair density measured by participants' self-assessment. Findings: Seventy-three women participated in this study. Primary hair count and thickness were 118.5 ± 10 hairs/cm2 and 58.8 ± 5.8 μ that changed to 124 ± 11 hairs/cm2 and 62.3 ± 4.3 μ respectively (P < 0.001) which in the zinc plus pantothenate group these changes were from 118.6 ± 9.9 hairs/cm2 to 121.9 ± 11.1 hairs/cm2 (P = 0.042) and from 62.2 ± 6.6 μ to 64.0 ± 5.0 μ (P = 0.126), respectively. Hair density increments were more obvious in the minoxidil group, and hair thickness increments were more obvious in pantothenate group. Participants' satisfaction was 85% in the combination therapy which was more than other groups. Participants' satisfaction, author's and blind dermatologist's opinion showed a significant correlation (P = 0.0001). Conclusion: Based on the participants' satisfaction, the combination of zinc sulfate and calcium pantothenate when administered in a pulse therapy way could be a good choice for hair loss controlling in initial stages.